Mathematics
Rina1233456
34

how to solve this equation showing step by step. 3(t - 1) = 9 + t

+3
(2) Answers
AQK24

1st: Expand the bracket 3t-3=9+t 2nd: Add the 3 to get rid of it on the first side. Do this to both sides 3t=12+t 3rd: Take away the t on the left hand side and one on the right hand side to just be left with t's on one side and integers on the other side 2t=12 4th: Divide both sides by 2 to find 1t t=6 Hope this helps!! :)

whiteheadkatie

3(t-1)=9+t 3t-3=9+t 3t-t=3+9 2t=12 (divide both sides by 2) t=6

Add answer